Budding of the Alveolate Alga Vitrella brassicaformis Resembles Sexual and Asexual Processes in Apicomplexan Parasites - Füssy, Zoltán; Masařová, Petra; Kručinská, Jitka; Esson, Heather J; Oborník, Miroslav (Protist, 2017)
Ease of cultivation and availability of genomic data promoted intensive research of free-living phototrophic relatives of apicomplexans, i.e. Chromera velia and Vitrella brassicaformis. Chromera and Vitrella differ significantly in their physiology, morphology, phylogenetic position and genomic features, but Vitrella has not gained as much attention. Here we describe two types of Vitrella zoosporangia. One contains zoospores surrounded by roughly structured matter, with an intracytoplasmic axoneme predicted to develop into a mature flagellum upon spore release, similarly to Plasmodium microgametes; in the second type, cells concurrently bud off the center of the sporangium, surrounded by smooth matter, and flagella develop extracellularly. This process of budding is reminiscent of microsporogenesis as seen in Toxoplasma. We suggest one (or both) of these processes generates gamete-like flagellate progeny. Based on live staining, fusion of zoospores does occur in cultures of V. brassicaformis. We failed to find an apical structure similar to the pseudoconoid in any life stage. V. brassicaformis may therefore either represent an ancestral state lacking an apical complex or has lost the apical complex secondarily. We propose that the common ancestor of Apicomplexa and "chrompodellids" exhibited a complex life cycle, which was reduced in chromerids and colpodellids as dictated by their environment.
Keywords: ciliogenesis.; Apicomplexa; Life Cycle Stages; zoosporangium; biologická evoluce; zoospores; Alveolata; Biological Evolution; Vitrella brassicaformis; Reproduction, Asexual; nepohlavní rozmnožování; budding; life cycle; stadia vývoje